Viruses and cancer - Weiss, Robin (Henry Stewart Talks, 2007)
Oncogenic viruses of animals and humans have given us insights into cancer in general, Specific genes involved in cancer such as oncogenes and tumor suppressor genes were first discovered through research on tumor viruses, Only a subset of viruses cause cancer, For cancers caused by viruses, the viruses are a necessary but insufficient cause of the disease, Cancer is multifactorial and different risk factors act together, Vaccines hold great promise to reduce the cancer burden, The incidence is higher in immunodeficient people, Transplant recipients and AIDS
Reviewed at 2020/08/16